2006
DOI: 10.1021/ol060926x
|View full text |Cite
|
Sign up to set email alerts
|

Hirsutellone F, a Dimer of Antitubercular Alkaloids from the Seed Fungus Trichoderma Species BCC 7579

Abstract: [structure: see text] Hirsutellone F (7), a novel alkaloid dimer, was isolated together with known monomers, hirsutellones A (1), B (2), and C (3), from the seed fungus Trichoderma sp. BCC 7579. The structure of 7 was elucidated by spectroscopic analysis. Studies on biomimetic chemistry, using the dimer 7, suggested that compound 8 (17,1'-dehydrohirsutellone B) should be the precursor for all hirsutellones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
58
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 7 publications
0
58
0
Order By: Relevance
“…Their structures were elucidated by interpretation of their spectroscopic data [70]. As a part of a continuing search for biologically active compounds from bioresources in Thailand [71][72][73], Berkaew et al have investigated the constituents of the wood-decay fungus Hypocrea sp. BCC 14122 (Hypocreaceae), since an extract of this strain had shown activity against human small cell lung cancer cells (NCI-H187, IC 50 = 5.2µg/mL).…”
Section: Figure 18mentioning
confidence: 99%
“…Their structures were elucidated by interpretation of their spectroscopic data [70]. As a part of a continuing search for biologically active compounds from bioresources in Thailand [71][72][73], Berkaew et al have investigated the constituents of the wood-decay fungus Hypocrea sp. BCC 14122 (Hypocreaceae), since an extract of this strain had shown activity against human small cell lung cancer cells (NCI-H187, IC 50 = 5.2µg/mL).…”
Section: Figure 18mentioning
confidence: 99%
“…The planar structure of 1 was deduced by analysis of its 1 H and 13 C NMR spectra (Table 1), 1 H– 1 H COSY and HMBC data (Figure 1), and comparison of these data with those reported for related fungal alkaloids. 8,1013 In its 1 H– 1 H COSY spectrum, 1 showed the presence of the spin systems CH 3 CH–, –CH 2 CHCH–, –CHCHCHCHCH(CH 3 )CH 2 CH(CH 3 )CH 2 CHCH–, and that due to a 1,4-disubstituted benzene ring. These data also suggested that 1 contained a succinimide moiety (δ c 171.6 and 177.3) and a tetracyclic cyclopenta[b]fluor-2(3),5(6)-diene ring system bearing six methyl groups at C–1, C–2, C–4, C–6, C–10, and C–12 and that the CH of CH 3 CH– spin system is a part of the tetracyclic ring (Figure 1).…”
mentioning
confidence: 99%
“…GKK1032, 10 pyrrocidines A and B from LL -Cyan 426, 11 hirsutellones A–E from Hirsutella nivea BCC7579, 12 hirsutellone F from Trichoderma sp. BCC 7579, 13 pyrrospirones A and B from Neonectria ramulariae , 14 all bearing a macrocyclic ether and succinimide-derived moieties are known, it is noteworthy that only embellicines A and B from Embellisia euerka 8 have been previously reported to contain the cyclopenta[b]fluorene (6/5/6/5) ring system encountered in phomapyrrolidones A–C ( 1–3 ).…”
mentioning
confidence: 99%
“…Heterodimeric hirsutellone F ( 4 ) and 17,1′-dehydrohirsutellone B ( 5 ), 2 the putative biosynthetic precursor to hirsutellones 1 – 4 (Scheme 1), were recently added to the growing class of hirsutellones [A ( 1 ), B ( 2 ) and C ( 3 ), 1 Scheme 1]. Isolated from the seed fungus Trichoderma sp.…”
mentioning
confidence: 99%
“…BCC 7579 incubated in a bioreactor (as opposed to incubation in an Erlenmeyer flask) by Isaka and coworkers, hirsutellone F ( 4 ) was shown to decompose to its apparent components, 17,1′-dehydrohirsutellone B ( 5 ) and hirsutellone A ( 1 ), upon exposure to basic conditions as shown in Scheme 1. 2 When the decomposition of 4 was carried out in the presence of NaBH 4 , hirsutellone B ( 2 ) was obtained in addition to hirsutellone A ( 1 ). Furthermore, it was determined that when the basic decomposition of 4 was performed in the presence of H 2 O 2 -NaOH, hirsutellone C ( 3 ) was generated together with hirsutellone A ( 1 ).…”
mentioning
confidence: 99%